Yield curve prediction for the strategic investor - Carlos Bernadell; Joachim Coche; Ken Nyholm (European Central Bank (ECB), 2005)
This paper presents a new framework allowing strategic investors to generate yield curve projections contingent on expectations about future macroeconomic scenarios. By consistently linking the shape and location of yield curves to the state of the economy our method generates predictions for the full yield-curve distribution under different assumptions on the future state of the economy. On the technical side, our model represents a regimeswitching expansion of Diebold and Li (2003) and hence rests on the Nelson-Siegel functional form set in state-space form. We allow transition probabilities in the regimeswitching set-up to depend on observed macroeconomic variables and thus create a link between the macro economy and the shape and location of yield curves and their time-series evolution. The model is successfully applied to US yield curve data covering the period from 1953 to 2004 and encouraging out-of-sample results are obtained, in particular at forecasting horizons longer than 24 months.
Keywords: C51; C53; E44; 330; Regime switching; scenario analysis; state space model; yield curve distributions; Zinsstruktur; Rendite; Kapitaleinkommen; Prognose; USA; Zustandsraummodell